VD_FINDINFO HC / 2016 / 85 vom 26. November 2015 - VD Tribunal cantonal (2015)
BAIL À LOYER, DÉFAUT DE LA CHOSE, ACCORD DE VOLONTÉS, UTILISATION | 153 al. 2 CPC (CH), 308 al. 1 let. a CPC (CH), 317 al. 1 CPC (CH), 317 al. 2 CPC (CH)